A mathematical model of semantic access in lexical and semantic decisions - Sergio E. Chaigneau; Nicolás Marchant; Enrique Canessa; Nerea Aldunate (Language and Cognition)
In this work, we use a mathematical model of the property listing task dynamics and test its ability to predict processing time in semantic and lexical decision tasks. The study aims at exploring the temporal dynamics of semantic access in these tasks and showing that the mathematical model captures essential aspects of semantic access, beyond the original task for which it was developed. In two studies using the semantic and lexical decision tasks, we used the mathematical model’s coefficients to predict reaction times. Results showed that the model was able to predict processing time in both tasks, accounting for an independent portion of the total variance, relative to variance predicted by traditional psycholinguistic variables (i.e., frequency, familiarity, concreteness imageability). Overall, this study provides evidence of the mathematical model’s validity and generality, and offers insights regarding the characterization of concrete and abstract words.